Effect of Hematology and Biochemistry during Lactation and Non-Lactation in Rhesus Monkey (Macaca Mullata ) (Journal of Laboratory Animal Science, 2025)
Lactation induces physiological changes in mammals, which can influence hematological and biochemical parameters. This study aims to compare the hematological and biochemical profiles of lactating and non-lactating Rhesus monkeys (Macaca mulatta) to better understand the impact of lactation on their metabolic and physiological status. The aims of this study were to verify if significant changes occur in hematological and biochemical parameters in Rhesus Macaques during Lactation period and Post lactation Hematological and biochemical parameters were evaluated in 12 Female Rhesus Macaques that were Lactating and Post Lactation .On Hematology analysis we could find the significant changes in neutrophil and Lymphocytes count between the two groups . Biochemistry analysis showed significant changes in Triglycerides level . Our findings provide reference data for researchers and contribute to a better understanding of pri mate biology in different reproductive states
Keywords: Macaca Mulatta; Lactation; Hematology; Biochemistry